2022
DOI: 10.21037/jtd-22-1113
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor antigens and immune subtypes in lung squamous cell carcinoma for mRNA vaccine development

Abstract: Background: Cancer vaccines are therapies that activate the patient's own immune system by inoculating the patient with cancer-specific antigens to identify and clear cancer cells. Messenger ribonucleic acid (mRNA) vaccines have received much attention because of their ease of synthesis, relative affordability, and long-term safety, but have not been studied in lung squamous cell carcinoma (LUSC). Thus, the identification of tumor antigens is necessary to facilitate the development of mRNA vaccines for LUSC.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Those are primarily bioinformatics-based studies that used genomic data from publicly available datasets on genetic alterations for NSCLC [35]. Candidate targets are usually selected as those targets with a positive correlation with the filtration of immune cells and confirmed to induce APCs expression upon their appearance [35][36][37][38][39]. Researchers also seek to identify the expression patterns of NSCLC that might benefit from treatment with mRNA vaccination [35][36][37][38][39].…”
Section: Recent Advances In Preclinical Research Of Mrna Vaccines For...mentioning
confidence: 99%
See 1 more Smart Citation
“…Those are primarily bioinformatics-based studies that used genomic data from publicly available datasets on genetic alterations for NSCLC [35]. Candidate targets are usually selected as those targets with a positive correlation with the filtration of immune cells and confirmed to induce APCs expression upon their appearance [35][36][37][38][39]. Researchers also seek to identify the expression patterns of NSCLC that might benefit from treatment with mRNA vaccination [35][36][37][38][39].…”
Section: Recent Advances In Preclinical Research Of Mrna Vaccines For...mentioning
confidence: 99%
“…Another two genes with prognostic value, ZC3H12D and TXNDC5, were identified in a study by Zhao et al as potential targets for lung adenocarcinoma vaccines, based on their correlation with APC infiltration and tumor purity [38]. Finally, in a study that focused on lung squamous carcinoma, it was demonstrated that the expression patterns of the genes bone morphogenetic protein 5 (BMP5) and claudin 5 (CLDN5) were positively correlated with antigen-presenting cell infiltration, indicating their potential for development as mRNA cancer vaccines [39].…”
Section: Recent Advances In Preclinical Research Of Mrna Vaccines For...mentioning
confidence: 99%